Multifocal Gastric Neoplasia after Recurrent Laser Therapy for the Watermelon Stomach. (1st August 1997) - Bernstein, Charles N; Pettigrew, Norman; Wang, Kenneth K; Greenberg, Howard; Lipschitz, Jeremy
Abstract : Repeated laser therapy has become an accepted therapeutic approach in the treatment of watermelon stomach, and to date no important negative sequelae have been reported. The case of a patient who underwent repeated sessions of neodymium: yttrium aluminum garnet (Nd:YAG) laser therapy over a five-year period for the treatment of the watermelon stomach is presented. Postlaser therapy the patient developed deep ulcerations that would heal; however, he ultimately developed a nodular antrum. Random biopsies of antral nodules revealed carcinoma-in-situ. A Billroth I gastrectomy revealed two foci of carcinoma-in-situ/high grade dysplasia and multiple foci of lower grades of dysplasia. This case suggests a possible association between use of laser therapy and development of gastric neoplasia.